PPP Comparative Study based on Type, Terminology, and Model Adaptation - Zahir, Asadullah; Chaturvedi, Ramesh Kumar (International Journal of Engineering and Management Research, 2025)
Public-private partnerships (PPPs) have emerged as a crucial mechanism for infrastructure development, particularly in nations facing fiscal constraints and technical limitations. This study conducts a comparative analysis of PPP projects globally, focusing on three critical aspects: types of models, adaptability of models, and the terminology used. Various countries define and implement PPP differently, influenced by their legal frameworks, economic conditions, and project-specific needs. The study aims to identify the different characteristics of the PPP model, the highly adaptive model, and the various terminologies used for PPP. The research identifies a formula for determining PPP models based on asset involvement, partner participation, and payment mechanisms. Findings reveal that greater private sector involvement correlates with higher PPP adaptability models, such as Build-Operate-Transfer (BOT) and Design-Build-Finance-Operate-Maintain (DBFOM) are among the most widely adopted. Additionally, the study highlights the inconsistencies in PPP terminology across different jurisdictions, underscoring the need for a globally unified framework to enhance efficiency and cross-border collaboration, reinforcing the necessity for standardized policies to streamline global PPP implementation.